Determination of optimal operating conditions for bioelectrolyte fuel cells using ADH as anode catalyst and solidification of fuel - Yusuke Takahashi; Hitoki Semizo; Yasumitsu Matsuo (Chemical Physics Impact)
Enzyme-based direct ethanol fuel cells (DEFCs) have the potential to become the next generation of energy devices without platinum catalysts. However, the development of DEFCs requires the search for new electrolytes that are compatible with ethanol fuel and enzymes. In this study, DEFCs with a combination of chitin electrolytes and ADH were fabricated and characterized. DEFCs using chitin electrolyte were also investigated for various ethanol fuel concentrations, and it was found that DEFCs using 50 mM ethanol achieved the highest power density. In addition, enzyme activity was measured and showed a maximum value when 50 mM ethanol was used, suggesting that the proton production reaction catalyzed by the enzyme determines the maximum power density of the bioelectrolyte DEFC. Furthermore, we successfully fabricated a highly portable solid bio-electrolyte DEFC and found that it achieved a maximum power density of 0.11 mW/cm2 at an ethanol concentration of 25 %.